Effect of cryotop vitrification method on oocytes at different meiotic stages and embryo development in vitro - XIANGCHEN, LI; YAXIN, YAO; YIPENG, WANG; HEPING, LI; WEIJUN, GUAN; YUEHUI, MA (The Indian Journal of Animal Sciences, 2012)
The effectiveness of existing procedures based on viable embryos per oocyte frozen remains low compared to use of fresh oocytes in cattle, and the probable causes of the freezing-induced reduction in oocyte developmental competence include chromosome, cytoskeleton disruption, or even the choice of the frozen stage of the oocytes. In the present study, after vitrification, the survival rate of GV and MI oocytes were significantly lower than those in MII. The vitrifid GV oocyte showed some chromosomes dispersed and less condensed, The vitrifid MI oocytes with “Fading’’ and discontinuous staining pattern were as having an abnormal microfilament distribution. The stage of GV and MI, both cleavage rate and blastocyst formation rate were reduced significantly. Therefore, the cryopreservation of GV or MI oocytes seems could not instead of the MII oocytes.